1990
DOI: 10.1128/aem.56.2.401-408.1990
|View full text |Cite
|
Sign up to set email alerts
|

Transport of a genetically engineered Pseudomonas fluorescens strain through a soil microcosm

Abstract: Vertical soil microcosms flushed with groundwater were used to study the influence of water movement on survival and transport of a genetically engineered Pseudomonas fluorescens C5t strain through a loamy sand and a loam soil. Transport of cells introduced into the top 1 cm of the vertical soil microcosms was dependent on the flow rate of water and the number of times microcosms were flushed with groundwater. The presence of wheat roots growing downward in the microcosms contributed only slightly to the movem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(59 citation statements)
references
References 45 publications
3
56
0
Order By: Relevance
“…Water flow rate, as governed by the intensity of rainfall, will also affect the rate and extent of translocation with faster flow rates increasing movement of both bacteria (Wollum and Cassel, 1978;Trevors et al, 1990;Huysman and Verstraete, 1993b) and viruses (Lance and Gerba, 1980;Lance et al, 1982). Field studies support these observations.…”
Section: Soil Water Content and Water Flowmentioning
confidence: 87%
See 3 more Smart Citations
“…Water flow rate, as governed by the intensity of rainfall, will also affect the rate and extent of translocation with faster flow rates increasing movement of both bacteria (Wollum and Cassel, 1978;Trevors et al, 1990;Huysman and Verstraete, 1993b) and viruses (Lance and Gerba, 1980;Lance et al, 1982). Field studies support these observations.…”
Section: Soil Water Content and Water Flowmentioning
confidence: 87%
“…In addition to soil water content, percolating water, either in the form of irrigation or rainfall will affect translocation through the soil matrix. Trevors et al (1990) showed that in the absence of downward water flow, movement of a Pseudomonasfluorescens strain in soil columns was negligible, whereas following percolation the bacterium could be detected throughout the soil column and in the leachate. Similarly, Madsen and Alexander (1982) showed increased movement of both Rhizobium and Pseudomonas following percolation of soil cores.…”
Section: Soil Water Content and Water Flowmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, possible effects of the vessel wall are more likely to occur in smaller systems. Both problems have been addressed in a previous paper [30], in which it was shown the experimental set-up used here did not suffer from a significant wall effect. In addition, repacked small soil columns do permit the study of particular factors under controlled environmental conditions.…”
Section: Discussionmentioning
confidence: 88%